Geographical Weighted Regression of Risk Factor of Stunting in Malang Regency, Indonesia - Yudono, Adipandang; Purnomo, Joko; Damayanti, Ratnaningsih (Forum Geografi, 2021)
Stunting has become a global concern. The incidence of stunting globally contributes to 15% of under-five mortality, with 55 million children losing their health (Bhutta, 2013) and it is estimated to reduce the country's GDP level up to 7% (Galasso and Wagstaff, 2018). In Indonesia, the incidence of stunting has become one of the main health problems that needs to be solved immediately. Malang Regency is one of the districts in East Java Province that has received the spotlight regarding the problem of stunting. It is estimated by the Regent of Malang Regency that there were 30,323 toddlers from a total of 154,188 toddlers in Malang Regency who are stunted (Plenary Meeting of the Malang Regency DPRD, 2018). This stunting rate in 2018 generated confusion because based on data from the Malang Regency’ People Representative Assembly (DPRD), since 2017, Malang Regency has had no stunting problems as a result of the implementation of the Contraceptive for Women at Risk (CONTRA WAR) program and the Community-Based Integrated Epidemiological Surveillance program (SUTERA EMAS). This research was conducted to examine risk factors of stunting in Malang Regency through Geographical Weighted Regression (GWR). GWR was carried out to calculate the correlation between predetermined demographic variables (population density, education, early marriage), health variables (number of health facilities, number of health workers, access to health facilities, availability of clean water and sanitation, number of malnutrition) and economic variables (income, numbers of poor population, prosperous rice distribution) which are assumed to have an influence on the incidence of stunting.